2017
DOI: 10.1002/ps.4586
|View full text |Cite
|
Sign up to set email alerts
|

Sublethal effects of chlorantraniliprole on juvenile hormone levels and mRNA expression of JHAMT and FPPS genes in the rice stem borer, Chilo suppressalis

Abstract: Sublethal concentrations of chlorantraniliprole might upregulate the expression of JH biosynthesis genes and in turn result in an increase of JH level in C. suppressalis. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 45 publications
(99 reference statements)
2
13
0
Order By: Relevance
“…Chlorantraniliprole‐susceptible third‐instar larvae of C. suppressalis (LC 50 of 0.21 mg L −1 ) were used for insecticide treatment, as described previously . A stock solution of chlorantraniliprole was dissolved in N , N ‐dimethylformamide containing 0.1% Triton X‐100 and diluted with distilled water to give insecticide concentrations of 0.92 and 4.7 mg L −1 , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Chlorantraniliprole‐susceptible third‐instar larvae of C. suppressalis (LC 50 of 0.21 mg L −1 ) were used for insecticide treatment, as described previously . A stock solution of chlorantraniliprole was dissolved in N , N ‐dimethylformamide containing 0.1% Triton X‐100 and diluted with distilled water to give insecticide concentrations of 0.92 and 4.7 mg L −1 , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies in the past have found that insecticides affect JH 14–16 . Our research found that cyantraniliprole can significantly affect the 20E titer and 20E biosynthetic genes of the female B. dorsalis .…”
Section: Discussionmentioning
confidence: 47%
“…Our observation indicated that cyantraniliprole affected the fecundity of female B. dorsalis , while only the 20E titer of insect hormones changed significantly. The sublethal doses of insecticides can affect the fecundity of insects, 1–4 and change the concentration of insect hormones and the expression of hormone anabolism genes 14–16 . 20E plays an essential role in the reproduction of insect females, 41 regulating Vg expression, ovarian development, egg chamber progression, morphogenesis of follicular epithelium and eggshell formation 21,42,43 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we determined the bioactivity of itol A against S. frugiperda. An enzyme-linked immunosorbent assay (ELISA) [35][36][37][38] was used to evaluate the effects of itol A on the JH levels in S. frugiperda larvae. Subsequently, the expression levels of the essential enzyme genes in the JH signaling pathway (SfJHAMT, SfFPPS, SfJHE, SfJHEH, SfJHDK) were verified by real-time quantitative polymerase chain reaction (qPCR).…”
Section: Introductionmentioning
confidence: 99%